2019
DOI: 10.1523/jneurosci.0866-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Neurogenesis and Neural Circuit Formation in a Cuprizone-Induced Multiple Sclerosis Mouse Model

Abstract: Cognitive impairments are key features in multiple sclerosis (MS), a progressive disorder characterized by neuroinflammation-induced demyelination in the central nervous system. To understand the neural substrates that link demyelination to cognitive deficits in MS, we investigated hippocampal neurogenesis and synaptic connectivity of adult-born neurons, which play an essential role in cognitive function. The administration and withdrawal of the combination of cuprizone and rapamycin (Cup/Rap) in C57BL/6J male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…The CPZ group showed a significant reduction in cell proliferation and neuroblast differentiation in the dentate gyrus compared to that in the CTL group. This result is in agreement with previous studies showing that neurogenesis is decreased in cuprizone-treated mice [25,66,67]. We also observed that transient forebrain ischemia significantly increased cell proliferation and neuroblast differentiation in the dentate gyrus of the hippocampus, consistent with previous studies [68][69][70][71].…”
Section: Discussionsupporting
confidence: 94%
“…The CPZ group showed a significant reduction in cell proliferation and neuroblast differentiation in the dentate gyrus compared to that in the CTL group. This result is in agreement with previous studies showing that neurogenesis is decreased in cuprizone-treated mice [25,66,67]. We also observed that transient forebrain ischemia significantly increased cell proliferation and neuroblast differentiation in the dentate gyrus of the hippocampus, consistent with previous studies [68][69][70][71].…”
Section: Discussionsupporting
confidence: 94%
“…In contrast to our results showing no significant differences in the numbers of DCX + cells, reduced numbers of DCX + NPCs were reported in a 4-week 47 , and a 6-week 48 cuprizone model. Additionally, and Zhang and collaborators described a reversible loss of DCX staining after a 6-week treatment with 0.3% cuprizone alone or in combination with rapamycin 49 . These, seemingly, contradictory findings might be in part explained by differences in analysis methods and in cuprizone models, but this would need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Cuprizone (CZ) is a copper chelator that causes demyelination in the CNS, noted particularly in the corpus callosum (CC) but also seen in other CNS regions (Gudi et al, 2009;Kipp et al, 2009;Koutsoudaki et al, 2009;Steelman et al, 2012;McMurran et al, 2019). It is widely used as a model to study experimental strategies to prevent myelin loss or promote remyelination (Mason et al, 2000;Bai et al, 2016;Karamita et al, 2017;Mullin et al, 2017;Laflamme et al, 2018) and neuronal plasticity (Zhang et al, 2020) in the context of multiple sclerosis (MS). How chelating copper induces oligodendrocyte (OL) death is not understood (McMurran et al, 2019), despite extensive work on its use as a model to study remyelination.…”
Section: Introductionmentioning
confidence: 99%